Representations of dating apps for Brazilian users - Antônio Carlos de Barros Júnior; Larissa Maria de Castro Alves; Andrea Siomara de Siqueira; Mario Amore Cecchini (Revista Subjetividades, 2023)
The objective of this study was to investigate representations of dating apps for Brazilian users, and whether there were differences regarding sex, sexual orientation and age. It had quantitative and qualitative approaches. Instrument used for data collection was an online questionnaire. Spontaneous responses brought up representations linked to unspecified relationships, feelings of discomfort or suffering, and practicality. Most prevalent closed-question representations were practicality, getting initial information before meeting people and searching for a stable love relationship. Establishing a long-term relationship was more prevalent in women and heterosexuals in general; aiming for sex was more prevalent in men and homosexuals, and living veiled experiences that cannot be openly experienced in face-to-face life was more prevalent in homosexuals. There were little statistically significant differences related to age. Despite changes in contemporary love relationships, traditional social representations are still in place: linked to the search for an ideal partner (women) and for sex and a transgressive jouissance (men). Apps reflect search for practicality and utilitarianism of postmodern capitalism in large cities, but also fun and pastime.